Role and Function of T Cell-Derived Exosomes and Their Therapeutic Value - Yuanyuan Shao; Xiaofeng Pan; Rong Fu (Mediators of Inflammation)
Exosomes are membrane-bound extracellular vesicles that are produced in the endosomal compartment of most eukaryotic cells. Containing proteins, RNA, and DNA, exosomes mediate intercellular communication between different cell types by transferring their contents and thus are involved in numerous physiological and pathological processes. T cells are an indispensable part of adaptive immunity, and the functions of T cell-derived exosomes have been widely studied. In the more than three decades since the discovery of exosomes, several studies have revealed that T cell-derived exosomes play a novel role in cell-to-cell signaling, especially in inflammatory responses, autoimmunity, and infectious diseases. In this review, we will summarize the function of T cell-derived exosomes and their therapeutic potential.